Long-term dietary supplementation with plant-derived omega-3 fatty acid improves outcome in experimental ischemic stroke. (May 2021) - Bonetti, Nicole R.; Liberale, Luca; Akhmedov, Alexander; Pasterk, Lisa; Gobbato, Sara; Puspitasari, Yustina M.; Vukolic, Ana; Saeedi Saravi, Seyed Soheil; Coester, Bernd; Horvath, Carla; Osto, Elena; Montecucco, Fabrizio; et al.
Abstract: Background and aims: Early revascularization -the gold standard therapy for ischemic stroke- is often withheld in the elderly population due to high risk of complications. Thus, safe and effective preventive and therapeutic options are needed. The plant-derived omega-3-fatty-acid alpha-linolenic-acid (ALA) has emerged as a novel cardiovascular-protective agent. As of yet, little is known about its potential therapeutic effects on stroke. We hereby aimed to investigate the impact of a clinically relevant long-term dietary intervention with ALA on stroke outcome. Methods: Six month-old C57BL/6 wildtype males were either fed an ALA-rich (high ALA) or a control diet (low ALA) for 12 months. At 18 months, brain ischemia/reperfusion was induced by transient middle cerebral artery occlusion (tMCAO). Stroke size and neurological function were assessed. Functional blood-brain-barrier-(BBB) permeability and protein expression were assessed by immunohistochemistry. Baseline inflammatory markers were measured at 18 months. Results: High ALA-fed animals displayed decreased circulating TNF-α levels and Neutrophil-to-Lymphocyte Ratios at 18 months. Stroke size and neurological dysfunction were significantly reduced in high ALA-fed animals. Coherently to the reduced stroke size, functional BBB integrity and occludin endothelial expression were maintained by high ALA supplementation. Additionally, ALA reduced endothelial activation and thus recruitment and activation of macrophages and resident microglia. Finally, high ALA diet reduced the expression of BBB-degrading and neurotoxic MMP-3 and MMP-9. Conclusions: We demonstrate the beneficial effects of a clinically relevant and feasible dietary intervention with a safe and readily available compound in the setting of stroke. The protective effects observed with ALA supplementation may relate to blunting of inflammation and might pave the way for novel stroke treatments. Graphical abstract: Image 1 Highlights: Long-term alpha-linolenic acid dietary supplementation improves stroke outcome. Dietary alpha-linolenic acid reduces post-stroke blood-brain barrier impairment. Alpha-linolenic acid reduces cerebral endothelial activation and inflammation.